2019
DOI: 10.4102/sajems.v22i1.2230
|View full text |Cite
|
Sign up to set email alerts
|

The bidirectional relationship between entrepreneurial intention and entrepreneurial competencies for nascent and existing entrepreneurs

Abstract: Results:The findings provide evidence of a bidirectional relationship between entrepreneurial intention and various entrepreneurial competencies, and the outcome thereof might lead to an increased business start-up. The strongest positive relationships were observed between entrepreneurial intention and self-efficacy, opportunity recognition, conveying a compelling vision, value creation through innovation (observing customer usage) and perseverance. Previous scholars confirmed that self-efficacy is a strong p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Atiya and Osman (2021) found perseverance to significantly affect university students' formation of EI in Sudan and Oman. Evidence of a significant association between EI and perseverance is also supported by Botha and Taljaard (2019) by establishing perseverance as an entrepreneurial competency required to form an intent to develop a business. A study by Salisu et al (2020) concluded that entrepreneurs must be persistent in overcoming adversity and emerge stronger than before to achieve sustainable success.…”
Section: Perseverance and Entrepreneurial Intention (Ei)mentioning
confidence: 95%
See 1 more Smart Citation
“…Atiya and Osman (2021) found perseverance to significantly affect university students' formation of EI in Sudan and Oman. Evidence of a significant association between EI and perseverance is also supported by Botha and Taljaard (2019) by establishing perseverance as an entrepreneurial competency required to form an intent to develop a business. A study by Salisu et al (2020) concluded that entrepreneurs must be persistent in overcoming adversity and emerge stronger than before to achieve sustainable success.…”
Section: Perseverance and Entrepreneurial Intention (Ei)mentioning
confidence: 95%
“…Perseverance research is gaining popularity and has been proposed as a fundamental component of a multidimensional EO (Santos et al, 2020). Perseverance is a behavioral pattern that refers to staying focused and committed to a chosen course of action in the face of obstacles or other available options (Botha & Taljaard, 2019). In venture creation, perseverance is conceptualized as an individual's core competency to carry out entrepreneurial ventures continuously despite adversity and impediments that obstruct the effort (Santos et al, 2020).…”
Section: Perseverance and Entrepreneurial Intention (Ei)mentioning
confidence: 99%
“…According to Krueger, Reilly, and Carsrud [20], ESE is proposed as a major antecedent of the intention to become an entrepreneur. Botha and Taljaard [27] even identified a relationship between ESE and EI. Lans, Gulikers, and Batterink [28] suggested a direct link between students' ESE and their EIs.…”
Section: Introductionmentioning
confidence: 97%
“…That is, a lower level of fit or no fit results in lower entrepreneurial intention even if there is a high level of entrepreneurial self-efficacy. Botha and Taljaard (2019) even identified a moderate interrelationship between entrepreneurial self-efficacy and intention. This called for policymakers and educators to pay more attention to the effect of policies as well as curriculum design on entrepreneurial self-efficacy.…”
Section: Introductionmentioning
confidence: 98%